Influence of time evolution in the modulus of elasticity of concrete reinforced by carbon fibers - Branco, Luiz A. Melgaço N.; Chahud, Eduardo; Lahr, Francisco Antonio Rocco; Christoforo, André L.; Battistelle, Rosane Aparecida Gomes [UNESP]; Panzera, Tulio Hallak (Trans Tech Publications, 2015)
The modulus of elasticity is an important property for the behavior analysis of concrete structures. This research evaluated the strain difference between concrete specimens with and without the application of laminate carbon fiber composites as well as the variation time, in months, of the axial strength compression and modulus of elasticity. Through the experimental results, it is concluded that increases in compressive strength and modulus of elasticity are more significant in the specimens without reinforcement.
Keywords: Carbon fiber composite; Concrete; Elasticity modulus; Structural reinforcement